Improving Ethyl Acetate Production in Baijiu Manufacture by Wickerhamomyces anomalus and Saccharomyces cerevisiae Mixed Culture Fermentations. (13th January 2019) - Fan, Guangsen; Teng, Chao; Xu, Dai; Fu, Zhilei; Liu, Pengxiao; Wu, Qiuhua; Yang, Ran; Li, Xiuting
Abstract : Ethyl acetate content has strong influence on the style and quality of Baijiu . Therefore, this study investigated the effect of Saccharomyces cerevisiae Y3401 on the production of ethyl acetate by Wickerhamomyces anomalus Y3604. Analysis of cell growth showed that Y3401 influences Y3604 by nutrient competition and inhibition by metabolites, while the effect of Y3604 on Y3401 was mainly competition for nutrients. Mixed fermentation with two yeasts was found to produce more ethyl acetate than a single fermentation. The highest yield of ethyl acetate was 2.99 g/L when the inoculation ratio of Y3401:Y3604 was 1:2. Synergistic fermentation of both yeasts improved ethyl acetate production and increased the content of other flavor compounds in liquid and simulated solid-state fermentation for Baijiu . Saccharomyces cerevisiae had a positive effect on ethyl acetate production in mixed culture and provides opportunities to alter the aroma and flavor perception of Baijiu .